(untitled) (International Journal of Natural Sciences Research, 2017)
ZrTiO4 thin films were deposited by reactive dc magnetron co-sputtering method without heating. The crystal structure, surface morphology, thickness, optical and dielectric properties of the thin films were investigated. At sputtering currents above 2.0 A without heating ZrTiO4 thin film was crystallization of the orthorhombic phase (111). The values of refractive index were ranged between 2.01 and 2.23 (at 650 nm). The optical packing density values were ranged between 0.85 and 0.96. From this study, it was observed that the refractive index values were strongly dependent on packing densities. The high dielectric constant width decreases from 74.3 to 43.3 when sputtering current increases, which is higher than other research.